2D/3D Perovskites: Introduction of Hydrophobic Ammonium Salts with Halogen Functional Groups for High‐Efficiency and Stable 2D/3D Perovskite Solar Cells (Adv. Funct. Mater. 47/2019). (19th November 2019) - Liu, Guozhen; Zheng, Haiying; Xu, Xiaoxiao; Xu, Shendong; Zhang, Xianxi; Pan, Xu; Dai, Songyuan
Abstract : In article number 1807565, Xu Pan, Songyuan Dai, and co‐workers design novel type 2D/3D perovskites by firstly introducing hydrophobic ammonium salt cations with halogen functional groups into 3D perovskite. Owing to the notable hydrophobicity of alkylammonium cations with halogen functional groups and the formed 2D/3D perovskite structure, the highly efficienct 2D/3D perovskite solar cells exhibit superior moisture resistance and thermal stability.